ICT-Driven Development in India and Africa - Nirupam Bajpai; Abhishek Beriya; John Biberman; Anchal Sharma; Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
Information and Communications Technology (ICT) has developed into one of the most significant tools at India's disposal for confronting challenges of development and poverty alleviation. In particular, ICT has proven useful when applied to the fields of agriculture, education, health, governance, and urban development. In recent years, numerous African countries have likewise introduced ICT solutions to various development challenges. While these initiatives have made great contributions, African countries interested in improving their ICT for development programs would greatly benefit from strategic and technical cooperation with India. India faces similar development challenges in an environment of high geographical, social, and economic diversity, making it an ideal testbed for developing interventions which scale in the developing world. Programs which have proven themselves in this context could likely be smoothly adopted to the African context, accelerating the pace of development for African ICT solutions. Ideally, India and Africa could cooperate not just on developing individual platforms, but on formulating an ethical and strategic framework for ICT-driven development which encourages inclusion, respects privacy, and shapes both regions to meet the future demands of the global economy.
Keywords: 330